MELLO, Alex Fiuza de. Marx e a globalização. 1ªedição. São Paulo: Boitempo, 1999, 286p. - Medeiros, Daniel de Souza (Geografia em Atos (Online), 2001)
MELLO, Alex Fiuza de. Marx e a globalização. 1ªedição. São Paulo: Boitempo, 1999, 286p.